Eksistensi Hidayah Sebagai Prinsip Epistemologi Islam: Analisis Tentang Hubungan Hidayah Dan Ilmu Pengetahuan - Luthfi (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
The crisis of modern epistemology, rooted in the positivist-secular paradigm, has forcibly separated scientific facts from transcendental values, resulting in a loss of teleological orientation in science. This research aims to perform a philosophical reconstruction of the concept of hidayah, not merely as a theological dogma but as an active epistemological principle underlying the human cognitive process. Utilizing a qualitative-philosophicalmethod through library research, this study dissects authoritative classical and contemporary texts to uncover the organic relationship between hidayah and knowledge.The results indicate that hidayah functions as a "super-regulator"within the cognitive structure, integrating bayani, burhani, and irfani reasoning into a unified tawhidic epistemology. This study identifies a hierarchy of hidayah—ranging from the sensory level (hissiyyah) to direct divine assistance (ma'unah/taufiq)—asa catalyst for true objectivity that liberates reason from the biases of ego (nafs). The novelty of this research lies in the repositioning of hidayah as an epistemic variable that providesa teleological compassfor science, ensuring that scientific validity is measured not only through logical coherence and empirical verification but also through ontological alignment with revelation. The implicationsof this research emphasize the importance of curriculum integration in Islamic higher education based on the unity of qauliyah and kauniyah verses to foster civilized and ethical science